Efficacy of preemptive intravenous ibuprofen and dexketoprofen on postoperative opioid consumption in laparoscopic cholecystectomy: Randomized controlled study - Celaleddin Soyalp; Ahmet Murat Yayik; Ersoy Öksüz; Nureddin Yüzkat (PLoS ONE, 2025)
Background To compare the effects of preemptive single-dose intravenous (IV) ibuprofen and dexketoprofen on postoperative pain and opioid consumption in patients undergoing laparoscopic cholecystectomy (LCC). Methods The study included 90 patients aged 18–65 years with an ASA score of I or II who underwent LCC. Patients were equally divided into three groups: Control Group (Group P), 100 cc 0.9% NaCl was infused intravenously over 30 min, Dexketoprofen Group (Group D), 50 mg dexketoprofen in 100 cc 0.9% NaCl was infused intravenously over 30 min, and Ibuprofen Group (Group I), 800 mg ibuprofen in 100 cc 0.9% NaCl was administered intravenously over 30 min. Visual Analog Scale (VAS) scores and opioid requirement were recorded at 1, 2, 4, 6, 12 and 24 hours postoperatively. Results There was no significant difference between the Dexketoprofen and Ibuprofen groups with regard to VAS scores, whereas VAS scores were higher in the control group than other groups in the 1st, 2nd, 4th, 6th,12th, and 24th hours. In addition, fentanyl consumption was higher in the control group at 0–6 hours and at 24 hours compared to the other two groups. Conclusion Preemptive ibuprofen and dexketoprofen administration reduce pain scores and opioid consumption compared with the control group, however, they are non-inferiority to each other.